Compound-Specific Stable Isotope Analysis of Amino Acids in Pelagic Shark Vertebrae Reveals Baseline, Trophic, and Physiological Effects on Bulk Protein Isotope Records - Magozzi, Sarah; Thorrold, Simon R.; Houghton, Leah; Bendall, Victoria A.; Hetherington, Stuart; Mucientes, Gonzalo; Natanson, Lisa J.; Queiroz, Nuno; Santos, Miguel N.; Trueman, Clive N. (Frontiers in Marine Science, 2021)
Variations in stable carbon and nitrogen isotope compositions in incremental tissues of pelagic sharks can be used to infer aspects of their spatial and trophic ecology across life-histories. However, interpretations from bulk tissue isotopic compositions are complicated because of multiple influences, including variations in primary producer isotope values, diets and physiological processing of metabolites. Isotope compositions of individual amino acids can partition the isotopic variance in bulk tissue into components associated with primary production on the one hand, and diet and physiology on the other. The carbon framework of essential amino acids (EAAs) can be synthesised de novo only by plants and bacteria and must be acquired by consumers through the diet. Consequently, the carbon isotopic composition of EAAs in consumers reflects that of primary producers in the location of feeding, whereas that of non-essential amino acids (non-EAAs) is additionally influenced by trophic fractionation and isotope dynamics of metabolic processing. Here we challenge ecological inferences drawn from bulk tissue isotope data using amino acid data. We determined isotope chronologies from vertebrae of individual blue sharks and porbeagles from the North Atlantic. We measured carbon and nitrogen isotope compositions in bulk collagen and carbon isotope values of amino acids. Despite large variability in individual profiles, bulk analyses revealed common, broad ontogenetic patterns across individuals of both species. EAA δ13C patterns confirmed that some of the variance in bulk tissue may be ascribed to spatio-temporal baseline variations. However, while life-history movements inferred from bulk analyses in blue sharks were supported by EAA δ13C values, inferences for porbeagles were not, implying that the observed trends in bulk protein δ13C values in porbeagles are influenced by trophic or physiological factors, or are spurious effects. We explored variations in non-EAA δ13C values, searching for systematic variations that might imply common ontogenetic changes in physiological processing. Patterns were highly variable and did not contribute to residual variance in bulk protein δ13C values. Isotopic effects associated with metabolite processing may overwhelm spatial influences that are weak or inconsistently manifested in bulk tissue isotope values (as in porbeagles). However, interpreting mechanisms underpinning patterns in non-EAA remains challenging.